Regional Head Election During Covid-19 Outbreak in Sigi District and Palu City, Central Sulawesi, Indonesia - Ridhwan, Muhammad; Primayanti, Andi Dewi; Salurante, Belona Danduru; Famrizal, Andi (Jurnal Ilmu Hukum Kyadiren, 2024)
This research aims to determine the increase in community participation in the 2020 election in Central Sulawesi and find out the factors that influence the increase in community participation in the 2020 election. This research is also to find out how community participation in the 2020 election in Central Sulawesi is and what factors influence it. influencing increased public participation in the 2020 election. The method used in this research is mixed methods (combination method), which combines quantitative methods and qualitative methods to be used together in this research activity so that comprehensive, valid, reliable, and objective data is obtained. This year's regional head elections are very different from previous regional elections because this is the first time regional head elections have been held in the midst of the COVID-19 pandemic. With regard to the simultaneous regional elections in 2020, which also coincide with the COVID-19 pandemic, the government is also swiftly and precisely thinking about and anticipating that these regional elections must still be carried out. The simultaneous regional head elections will be held in 2020. With the COVID-19 pandemic, this will be less than optimal, and it is feared that it will limit the performance of the Pilkada implementers, which could also have an impact on the implementation of the Pilkada itself. The potential for regional election fraud to occur during the pandemic is very large.